2017
DOI: 10.31142/ijtsrd5914
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Requirements and Management Strategies for Fish Farming A Case Study of Ponds Around Gurgaon Canal NUH Palwal

Abstract: A study on standard water quality parameter requirements and management strategies suitable for fish farming is presented. The water quality criteria studied based on physical, chemical and biological properties of water include temperature, turbidity, total suspended solids (TSS), total dissolved solid (TDS), nitrate-nitrogen, pH, Dissolved oxygen (DO) biochemical oxygen demand (BOD) and total hardness. Water samples from around Gurgaon Canal in NCR union territerian New Delhi capital of India, were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
1
12
1
Order By: Relevance
“…The temperature of the Luvuvhu River as well as the fish ponds in Duthuni (21.4–22.5 °C) did not comply with the recommended limits of 25−30 °C [ 36 ] and 28−30 °C [ 37 ] for O. mossambicus farming. In a previous study, Khan et al [ 38 ] reported a water temperature in the range of 27.50–31.10 °C for fish ponds at Gurgaon canal in India. Oreochromis mossambicus require moderate temperature for reproduction, growth, metabolism and physiology [ 39 ] and rapid change of temperature interferes with their reproduction and growth [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The temperature of the Luvuvhu River as well as the fish ponds in Duthuni (21.4–22.5 °C) did not comply with the recommended limits of 25−30 °C [ 36 ] and 28−30 °C [ 37 ] for O. mossambicus farming. In a previous study, Khan et al [ 38 ] reported a water temperature in the range of 27.50–31.10 °C for fish ponds at Gurgaon canal in India. Oreochromis mossambicus require moderate temperature for reproduction, growth, metabolism and physiology [ 39 ] and rapid change of temperature interferes with their reproduction and growth [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although hardens >300 ppm is expected to be lethal to fish life as it increases the pH, Carb and Koi show tolerance to hardness in a way similar to some euryhaline species (Bhatnagar et al., 2004). It is also recommended to decrease the hardness of the water to reach the acceptable value by adding lime to the lake (Khan et al., 2017) before lake's fish culture.…”
Section: Resultsmentioning
confidence: 99%
“…It has a direct effect on fish growth and production of the aquaculture through feed consumption. Low DO level can be harmful to the culture fish because of the increase in the water toxicity level [21]. Conductivity is a measure of how well the water conducts electricity and is diretly related to salt content.…”
Section: The Monitoring Stationmentioning
confidence: 99%